2018
DOI: 10.1016/j.toxlet.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics profiling of steatosis progression in HepaRG ® cells using sodium valproate

Abstract: Non-alcoholic Fatty Liver Disease (NAFLD) is a frequently encountered Drug-Induced Liver Injury (DILI). Although this stage of the disease is reversible, it can lead to irreversible damage provoked by non-alcoholic steatohepatitis (NASH), fibrosis and cirrhosis. Therefore, the assessment of NAFLD is a paramount objective in toxicological screenings of new drug candidates. In this study, a metabolomic fingerprint of NAFLD induced in HepaRG cells at four dosing schemes by a reference toxicant, sodium valproate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…Among the 12 drugs, AMIO, ALLO, 5FU, INDI, INDO, METHO, SUL, RIF, and TRO induced steatosis in HepaRG cells, thus confirming that the HepaRG cell line represents a suitable model in order to study druginduced steatosis (Anthérieu et al 2011;Cuykx et al 2018;Tolosa et al 2016). In addition, we found that AMIO, ALLO, 5FU, INDI, INDO, RIF, and TRO also induced steatosis in at least one out of six different PHH batches.…”
Section: Discussionsupporting
confidence: 70%
“…Among the 12 drugs, AMIO, ALLO, 5FU, INDI, INDO, METHO, SUL, RIF, and TRO induced steatosis in HepaRG cells, thus confirming that the HepaRG cell line represents a suitable model in order to study druginduced steatosis (Anthérieu et al 2011;Cuykx et al 2018;Tolosa et al 2016). In addition, we found that AMIO, ALLO, 5FU, INDI, INDO, RIF, and TRO also induced steatosis in at least one out of six different PHH batches.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the ability of this model to detect delayed mitochondrial toxicity has been shown for a panel of mitotoxicants with varied mitochondrial targets, including mitochondrial DNA, mitochondrial protein synthesis and fatty acid oxidation 61,62 . Importantly, this model enabled the pathway of mitochondrial toxicity to be delineated at concentrations in the region of drug exposure (Cmax, Css) in clinical practice.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…The use of drugs is a frequent cause of steatosis, [17][18][19] ranging across multiple therapeutic classes including antiarrhythmic agents, chemotherapeutics, and tetracyclines. 6,[20][21][22] High doses and prolonged use of tetracycline, for treatment of a range of bacterial infections, 23 has been shown to cause steatosis and liver damage in animals [23][24][25][26] clinically similar to the human pathology of liver steatosis assessed by histological staining. [27][28][29] Animal studies play an important role in studying and understanding the pathogenic processes of the human disease.…”
Section: Introductionmentioning
confidence: 94%
“…6,20,21,25,31,32 Researchers have investigated altered chemical pathways 27,[33][34][35][36] drug-induced steatosis through metabolite changes in serum, urine and hepatic tissues from animals and patients. 19,22,24,25,[37][38][39][40][41] These studies have identied several metabolites associated with various pathways related to the pathogenesis of drug induced steatosis. However, these studies have limitations identifying changes in biomarkers in the early development and progression of the disease.…”
Section: Introductionmentioning
confidence: 99%